Designing a Training Model for Promoting Entrepreneurship at Grassroots Level Through Women Self Help Groups - Sivasubramanian, M. (AMC Indian Journal of Entrepreneurship, 2019)
In the past three decades, women self help groups have registered significant socio-economic changes at grassroots levels of the Indian economy. The unique structure which was designed to suit their requirement was one of the major reasons to make the program successful. Even though it has released the poor from the clutches of moneylenders, micro entrepreneurship needs to be nurtured to firm up sustained development. The author in this research work studied the members' entrepreneurial skills, entrepreneurial propensity, barriers to become entrepreneurs, and influence of group cohesiveness among members. The primary data were collected from statistically treated women self help groups through structured interview schedule. The study found that micro-entrepreneurs influence others to become entrepreneurs. On the basis of this, the new training model was designed to suit the requirement of women self help groups.